Dynamic simulation of the ultra-fast-rotating sandwich cantilever disk via finite element and semi-numerical methods - Wu, Jinhui; Habibi, Mostafa (Engineering with computers, 2022)
In the presented research, vibrational, and amplitude behaviors of a sandwich spinning disk made of two laminated layers and graphene nanoplatelets reinforced composite (GPLRC) core has been reported. The Coriolis and centrifugal impacts have been taken into account due to its rotational feature. The stresses and strains have been obtained through the high-order shear deformable theory (HSDT). The structure’s boundary conditions (BCs) are determined using laminated rotating disk’s governing equations employing energy methods and ultimately have been solved via a computational approach called generalized differential quadrature method (GDQM). The rotational disk’s vibrations with different BCs have been explained using the curves drawn by MATLAB programming. Moreover, the hinged BCs have been considered to edges θ = 3 π / 2 , and θ = π / 2 . Furthermore, cantilever (clamped–free) BCs, respectively, are taken into account in R = R i , and R 0 . In addition to computational approach, a 3-D finite element (FE) simulation has been conducted via ABAQUS software employing the FE package to model the laminated cantilevered disk’s response. The outcomes determined by a FE simulation demonstrate a decent agreement with the semi-numerical approach’s results. Thereby the results reveal, disk’s angle of ply, number of layers, length scale, angular velocity, and nonlocal elements, and geometrical features have a significant influence on the vibration and amplitude characteristics of a sandwich spinning Clamped-Free disk. As a practical outcome in pertained industries, If the structure is manufactured of an even layers’ number, the system’s frequency response would be much better, specifically in a small radius ratio amount.